Busco novio para mi mujer [videorecording (DVD)] - Begné, Enrique; Echeverría, Sandra, 1984-; Torre, Arath de la, 1975-; Ochoa, Jesús (Pantelion, 2016)
Pasco is so fed up with his nagging and nitpicking wife Dana that he comes up with an ingenious plan to end the unhappy union. He finds her a boyfriend by hiring a professional seducer nicknamed 'El Taiger' to whisk her off her feet and out of the marriage. But even the best laid plans can backfire when love is involved.